THE IMPACT OF SERVICE QUALITY AND OUTCOME QUALITY DIMENSIONS TOWARDS CUSTOMER LOYALTY THROUGH CUSTOMER SATISFACTION ON MID-LEVEL HOTELS. - Devi, Karina Vashti (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2023)
This study aims to analyze the effects of Service Quality dimensions and Outcome Quality dimensions on Customer Satisfaction and Customer Loyalty in three stars Hotels in Surabaya. Independent Variables used in this study are; Service Quality, with its dimensions; Tangibility, Reliability, Responsiveness, Assurance, and Empathy, and Outcome Quality, with its dimensions; Valence, Waiting Time, and Sociability. This study is a causal research and a quantitative method was used. Data are gathered by sharing online questionnaires. Service Quality dimensions oftentimes are referred to as the main factors that influence customer satisfaction. There’s only a small amount of research done about the influence of Outcome Quality and its dimensions on customer satisfaction, especially in Indonesia. This study’s findings will be about which service quality dimensions and outcome quality dimensions have the most influence on customer satisfaction in three-star Hotels in Surabaya, and the influence of customer satisfaction towards customer loyalty in three-star Hotels in Surabaya.